2019
DOI: 10.1039/c9cp02028d
|View full text |Cite
|
Sign up to set email alerts
|

Adiabatic deprotonation as an important competing pathway to ESIPT in photoacidic 2-phenylphenols

Abstract: ESIPT vs. ESPT: an adequate choice of the substitution pattern can take ESIPT to C-atom to another level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Similarly, the 550 nm emission is also blue-shifted compared to the TICT emission in a more polar protic solvent, methanol. This is consistent with the fact that with an increase in polarity the tautomer band undergoes a blue shift and the TICT band undergoes a red shift. ,,, The blue shift and the red shift indicate the increase and decrease in the energy gap between the ground and the excited state. This means that the excited state of the tautomer is less stabilized than its ground state in the polar environment, and it is just the opposite for the TICT state.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Similarly, the 550 nm emission is also blue-shifted compared to the TICT emission in a more polar protic solvent, methanol. This is consistent with the fact that with an increase in polarity the tautomer band undergoes a blue shift and the TICT band undergoes a red shift. ,,, The blue shift and the red shift indicate the increase and decrease in the energy gap between the ground and the excited state. This means that the excited state of the tautomer is less stabilized than its ground state in the polar environment, and it is just the opposite for the TICT state.…”
Section: Resultssupporting
confidence: 77%
“…It is also an important photoprocess and has wide applications in various fields including photoswitches. Highly Stokes-shifted tautomer emission is an additional advantage of ESIPT over isomerization. TICT depends on the strength of the electron-donor and -acceptor groups present in the fluorophore. ESIPT depends on the acidity and basicity of the groups those are connected by the intramolecular hydrogen bond. Hence, the strength of the charge transfer and intramolecular hydrogen bond determines the emission properties of the fluorophores. It is reported that in 4-(diethylamino)-2-hydroxybenzaldehyde and 2-(4′-diethylamino-2′-hydroxyphenyl)­benz-imidazole, the ESIPT process suppresses the charge-transfer process. , However, in the cases of 4-amino-2-hydroxybenzoicacid and 4-(dimethylamino)-2-hydroxybenzoicacid, the proton-transfer process accelerates the charge-transfer process. , In 5-diethylamino-2-[(4-diethylaminobenzylidene)­hydrazonomethyl]­phenol and N , N ′-bis­(4- N , N -diethylaminosalisalidene)­hydrazine Schiff bases, Guchhait et al demonstrated that the proton-transfer process assists in the charge-transfer process . 4-(Dimethylamino)-2-hydroxybenzoate has been reported to emit triple fluorescence .…”
Section: Introductionmentioning
confidence: 99%
“…PP is a classic example of photoacid so an acidity enhancement was observed upon photo-irradiation, resulting in a large p K a decline in the excited-state () of PP , as expected. 41,42 A solvent molecule and any basic participants can act as the proton acceptors for the photoinduced protons dissociated from the photoacid in the excited state. For some “super” photoacid compounds, reached values slightly greater than zero or even attained negative values.…”
Section: Resultsmentioning
confidence: 99%
“…This result is consistent with the previous studies on the occurrence of the ESPT process in an organic/ aqueous system in 2-phenylphenol and its derivates. [39][40][41][42] The fluorescent emission of unmodified AL has also been investigated to determine the fluorescence origin in the visible region. At F w = 0.95, AL shows very low emission intensity compared to AL-Por-PP-1 (Fig.…”
Section: Synthesis and Characterization Of Al-por-pps Nanohybridsmentioning
confidence: 99%
See 1 more Smart Citation